Unveiling the Drivers of Mergers and Acquisitions : The Mediating Role of Access to Resources - Jain, Divya; Maheshwari, Girish Chandra; Singh, Archana (Indian Journal of Finance, 2025)
Objective : This study explored the relationship between the objectives of mergers and acquisitions (M&A), post-acquisition performance, and the mediating effect of access to resources. It aimed to reveal how M&A transactions impacted organizational performance, providing strategic and managerial insights within the Indian context. Design/Methodology/Approach : This research relied on primary data collected through a well-designed questionnaire. Participants were selected using non-probability random sampling. Data interpretation and analysis were conducted using partial least squares structural equation modeling (PLS-SEM) software. Findings : While access to resources did not directly impact post-acquisition performance, mediator analysis revealed its statistical significance in the context of diversification, increased market power, and expansion. Practical Implications : The findings proposed valuable insights for the policymakers, investors, and shareholders involved in the acquisition processes. They aided them in making informed decisions at various stages of acquisition, which can help foster employee commitment and trust, thereby enhancing acquisition performance. Originality/Value : The research contributes to having deep insights into the relationships between different motivational factors for M&As and post-acquisition performance. Moreover, it introduces the novel concept of access to resources as a mediator between motivational factors and post-acquisition performance, offering unique insights into the context of India’s transitional economic growth and development.